What Is The Association Between Long-Term Intrauterine Device (IUD) Use And The Risk Of Developing Uterine Cancer In Women Aged 35-65? - Yunike Putri Nurfauzia; I Made Adi Saputra Wijaya; Mutia Juliana; Lina Haryani (International Medical Journal Corp. Ltd, 2025)
Introduction: Uterine cancer is a significant health concern, especially among women aged 35-65 years. Intrauterine devices (IUDs), including hormonal levonorgestrel-releasing intrauterine systems (LNG-IUS) and copper IUDs (Cu-IUD), are widely used for contraception and have been investigated for their potential role in reducing uterine cancer risk. Methods: A comprehensive review of studies published in the last decade was conducted, focusing on the association between long-term IUD use and uterine cancer risk in women aged 35-65. Studies included randomized controlled trials, prospective and retrospective cohorts, with follow-up durations ranging from six months to over ten years. Results: Evidence indicates that long-term use of both LNG-IUS and Cu-IUD is associated with a reduced risk of uterine cancer and its precursor lesions. LNG-IUS demonstrated superior efficacy compared to oral progestogens in treating atypical endometrial hyperplasia (AEH) and reducing cancer recurrence. Cu-IUD use was also linked to lower risks of endometrial and cervical cancers. Adverse events were generally mild, with weight gain being the most common side effect, and device-related complications such as expulsion and perforation were rare. Discussion: The protective effects of LNG-IUS are attributed to localized progestin release causing endometrial atrophy, while Cu-IUDs may exert effects through local inflammatory mechanisms. Despite promising findings, age-stratified data remain limited, and further long-term studies are needed. Conclusion: Long-term use of LNG-IUS and Cu-IUD offers effective contraception and a favorable reduction in uterine cancer risk with a good safety profile, supporting their role in preventive strategies for women aged 35-65.